Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.virol.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Pathological manifestations of feline immunodeficiency virus (FIV) infection in wild African lions

Abstract: Feline immunodeficiency virus (FIV) causes AIDS in the domestic cat (Felis catus) but has not been explicitly associated with AIDS pathology in any of the eight free-ranging species of Felidae that are endemic with circulating FIV strains. African lion (Panthera leo) populations are infected with lion-specific FIV strains (FIVple), yet there remains uncertainty about the degree to which FIV infection impacts their health. Reported CD4+ T-lymphocyte depletion in FIVple infected lions and anecdotal reports of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 79 publications
4
64
2
3
Order By: Relevance
“…Supporting the importance of host factors is the observation that lions infected by the lionadapted strain of FIV more frequently develop oral papillomas than do uninfected lions. 7 In the present case, FIV infection could be excluded only in cat No. 1, although neither cat showed other evidence of immunosuppression.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Supporting the importance of host factors is the observation that lions infected by the lionadapted strain of FIV more frequently develop oral papillomas than do uninfected lions. 7 In the present case, FIV infection could be excluded only in cat No. 1, although neither cat showed other evidence of immunosuppression.…”
mentioning
confidence: 63%
“…The oral papillomas of exotic felids are also histologically similar to those of domestic cats and, in contrast to most nonfeline species, typically contain prominent PV cytopathic changes. 7,9 As PVs within a genus tend to have the same tissue tropism and cause the same lesions, the similarities between the lambdapapillomavirus-induced oral papillomas of exotic felids and the oral papillomas in domestic cats provide further evidence that FcaPV-1 is the etiology of these lesions.…”
mentioning
confidence: 99%
“…To determine the lower limit of quantitation (LLOQ), PLV standards (diluted in TE buffer) were tested on multiple days to determine the lowest concentration that could consistently be quantified. Standard concentrations tested were 10 2 to 10 7 plasmid copies/well (10-fold dilutions), as well as values below this range (10,20,40,50,60, and 80 copies/well). The LLOQ was determined to be 10 2 copies/well, equivalent to 17,000 RNA copies/ml plasma.…”
Section: Table 3 Demographic Information For All Samples Included Inmentioning
confidence: 99%
“…Three out of four of the sampled lion populations had greater than 95% positivity for FIV [72]-such high prevalences along with signs of immune suppression in some non-captive African lions suggest that viral-associated lymphoma might be a problem for wild cat populations as well. A captive lion showing wasting, periodontitis and lymphadenopathy (similar to the wild lion findings of Roelke et al [72]) was found at autopsy to have lymphoma and was FIV positive [73]. However, a retrospective study in US zoos of captive-born African lions with lymphoma found no FIV in tumour samples; nor were any of the lions serologically positive for FIV, according to zoo records [74].…”
Section: Infectious Cancers In Vertebrates (A) Historical Trendmentioning
confidence: 98%
“…Although species-specific FIV infections in large, nondomestic cats have historically been considered mild, recent investigation of non-captive African lions found indicators of FIV-associated immune depletion [72]. Three out of four of the sampled lion populations had greater than 95% positivity for FIV [72]-such high prevalences along with signs of immune suppression in some non-captive African lions suggest that viral-associated lymphoma might be a problem for wild cat populations as well. A captive lion showing wasting, periodontitis and lymphadenopathy (similar to the wild lion findings of Roelke et al [72]) was found at autopsy to have lymphoma and was FIV positive [73].…”
Section: Infectious Cancers In Vertebrates (A) Historical Trendmentioning
confidence: 99%